Internal Factors Affecting the NPL of State-Owned Commercial Banks - Mohammad Sofyan; Bambang Heru Purwanto (Ilomata International Journal of Management, 2023)
Banking in Indonesia generally relies on loan interest income as the primary income in financing its operations. Not all credit extended is risk-free; some have sizable risks and can threaten the bank’s health. So to measure a bank's ability to overcome failure to take credit from debtors, the NPL ratio can be used. This study aims to analyse the influence of internal factors, namely: CAR, LDR, NIM, and OEOI, on NPLs of State-Owned Commercial Banks during 2015-2022. The research was conducted using a qualitative descriptive method with panel data using the financial statements of Bank BRI, Bank BNI, Bank Mandiri, and Bank BTN during 2015 - 2022. The results of this study indicate that CAR and BOPO have a significant positive effect on NPL, while LDR and NIM have a significant negative effect on NPL.